2017
DOI: 10.1177/1535370217707729
|View full text |Cite
|
Sign up to set email alerts
|

Roles of silent information regulator 1–serine/arginine-rich splicing factor 10–lipin 1 axis in the pathogenesis of alcohol fatty liver disease

Abstract: Impact statementALD is a major health burden in industrialized countries as well as China. AFLD, the earliest and reversible form of ALD, can progress to hepatitis, fibrosis/cirrhosis, even hepatoma. While the mechanisms, by which ethanol consumption leads to AFLD, are complicated and multiple, and remain incompletely understood. SIRT1, SFRS10, and LIPIN1 had been separately reported to participate in lipid metabolism and the pathogenesis of AFLD. Noteworthy, we found the connection among them via searching ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
(216 reference statements)
0
3
0
Order By: Relevance
“…Small noncoding RNA, such as miRNAs, suppressed the expression of target genes at the translation level by affixing to the 3′ untranslated region (UTR) mRNAs leading to the degradation of the target mRNA [12]. Sirtuin 1 (SIRT1), a deacetylase enzyme that relies on nicotinamide adenine dinucleotide (NAD + ), is essential in several cellular mechanisms, like oxidative stress, inflammation, and fibrosis [13][14][15]. A recent study has shown that miR-34a-5p can induce renal fibrosis by downregulating SIRT1 expression [16].…”
Section: Introductionmentioning
confidence: 99%
“…Small noncoding RNA, such as miRNAs, suppressed the expression of target genes at the translation level by affixing to the 3′ untranslated region (UTR) mRNAs leading to the degradation of the target mRNA [12]. Sirtuin 1 (SIRT1), a deacetylase enzyme that relies on nicotinamide adenine dinucleotide (NAD + ), is essential in several cellular mechanisms, like oxidative stress, inflammation, and fibrosis [13][14][15]. A recent study has shown that miR-34a-5p can induce renal fibrosis by downregulating SIRT1 expression [16].…”
Section: Introductionmentioning
confidence: 99%
“…In the early stages, ALD typically manifests as steatosis superimposed by an inflammatory infiltrate and progresses to fibrosis or cirrhosis with continued alcohol intake [2]. Excessive drinking can cause alcoholic fatty liver within 2 or 3 weeks and may have further effects on the immune system [3]. Alcohol consumption is also highly correlated with the progression of alcoholic fatty liver [4], causes liver damage, and helps to enhance the production of proinflammatory cytokines and chemokines [5,6], which can enhance the concentration of macrophages and neutrophils for promoting the inflammation response [7].…”
Section: Introductionmentioning
confidence: 99%
“…Alcoholic liver disease (ALD), a disease originating from excessive alcohol consumption, is one of the major cause of morbidity and mortality of clinical liver disease worldwide. 1,2 ALD comprises a spectrum of disease ranging from steatosis, fibrosis, to alcoholic hepatitis (AH), cirrhosis and its complications . 3 Not all the heavy alcohol consumers could progress to the liver steatosis, more than 90% of alcohol consumers developing into fatty accumulation and only 30% Jinhui Sun and Baolong Li have contributed equally to this study.…”
Section: Introductionmentioning
confidence: 99%
“…Alcoholic liver disease (ALD), a disease originating from excessive alcohol consumption, is one of the major cause of morbidity and mortality of clinical liver disease worldwide . ALD comprises a spectrum of disease ranging from steatosis, fibrosis, to alcoholic hepatitis (AH), cirrhosis and its complications .…”
Section: Introductionmentioning
confidence: 99%